IMPROVING THE LISTENING COMPETENCE OF THE TENTH GRADE STUDENTS’ OF SMK NEGERI 1 NUSA PENIDA BY USING STORY BASED AUDIO VISUAL MATERIALS. - ., I Komang Alit Putra; ., Drs. I Wayan Suarnajaya,MA., Ph.D.; ., I Putu Ngurah Wage M, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk meningkatkan kemampuan siswa dengan menggunakan story berdasarkan materi audio visual. Subjek penelitian ini adalah siswa kelas sepuluh multimedia di SMK Negeri 1 Nusa Penida, tahun akademik 2015/2016. Jumlah subjek penelitian ini adalah 24 siswa. Penelitian ini di desain menggunakan penelitian tindakan kelas dimana dilakukan dalam dua siklus. Tiap siklus berisi empat langkah seperti: perencanaan, tindakan, observasi, dan refleksi. Data di analisis deskirptif yang mana diperoleh dengan menggunakan dua jenis instrument: test dan questionnaire. Hasil penelitian ini menunjukkan bahwa cerita berdasarkan materi audio visual meningkatkan kemampuan siswa di dalam mendengarkan. Peningkatan siswa di lihat dari skor rata-rata yang diperoleh siswa. Skor rata-rata pre-test adalah 46,16 dan ini dalam tingkat kurang. Peningkatan Skor menjadi 61,00 di post test 1 yang mana berada di tingkat baik. Peningkatan skor menjadi 68,50 berada di tingkat baik. Dari penjelasan diatas, dapat disimpulkan bahwa memiliki pengaruh yang positif untuk meningkatkan kemampuan siswa dalam hal mendengarkan. Mengajarkan mendengarkan dengan menggunakan cerita berdasarkan materi audio visual material menarik minat siswa dalam meningkatkan kemampuan mendengarkan siswa. Kata Kunci : Kemampuan Mendengarkan, Cerita berdasarkan Materi Audio Visual In this research, the researcher used story based audio visual materials to improve students’ listening competence. The participants were the students of the tenth grade students of SMK Negeri 1 Nusa Penida in academic year 2015/2016. The subjects consisted of 24 students with 10 females and 14 males. This research was designed in the form of classroom action research (CAR) which was conducted in two cycles. There were 4 phases included, namely planning, action, observation, and reflection. The data obtained were analyzed descriptively. The mean score of the pre test was 46.16 which means that some of the students or 41% could pass the minimum score level of criteria (KKM) and it was categorized as poor level. Meanwhile, the mean score of the post test 1 was 61.00 which means that there were 12 students or 50% who could pass KKM and it indicated that students’ level was sufficient. After post test 2 was conducted, the mean score increased up to 68.50 which means that there were 19 students or 79% could pass KKM. The score of the post test 2 was categorized as good level. Based on the explanation above, it can be said that story based audio visual materials have positive influence for improving students’ listening competence in post test. It can help students improve their ability in listening. Then, teaching listening by using story based audio visual materials attracted the students’ attention in improving their listening competence. keyword : Listening Competence, Story based Audio visual Materials